2021
DOI: 10.1111/jcmm.16784
|View full text |Cite|
|
Sign up to set email alerts
|

LINC00472 suppressed by ZEB1 regulates the miR‐23a‐3p/FOXO3/BID axis to inhibit the progression of pancreatic cancer

Abstract: The tumour‐suppressive role of LINC00472 has been extensively reported in various human cancers such as lung, colon and ovarian cancers, yet its function in pancreatic cancer remains unidentified. Here, the current research aimed to explore the role and regulatory axis mediated by LINC00472 in the progression of pancreatic cancer. RT‐qPCR was adopted to determine LINC00472 expression in the harvested pancreatic cancer tissues and adjacent normal tissues. Loss‐of‐function and gain‐of‐function experiments were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…FOXO3 is known to be a key regulator in cell growth. 24 In our research, FOXO3 was identified to be the direct target of miR-1281. It has been reported that FOXO3 participate in cell pyroptosis.…”
Section: Discussionmentioning
confidence: 67%
“…FOXO3 is known to be a key regulator in cell growth. 24 In our research, FOXO3 was identified to be the direct target of miR-1281. It has been reported that FOXO3 participate in cell pyroptosis.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, it is vital to evaluate the mechanisms of PC progression and to establish novel treatment targets for improving survival outcomes of PC patients. In a previous study, RT-qPCR analysis revealed that LINC00472 levels in pancreatic cancer tissues were suppressed, relative to adjacent normal tissues ( Bi and Wang, 2021 ). Moreover, the study identified correlations between LINC00472 low expressions and TNM stages, lymph node metastases and overall survival outcomes but not with gender and age ( Bi and Wang, 2021 ).…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, RT-qPCR analysis revealed that LINC00472 levels in pancreatic cancer tissues were suppressed, relative to adjacent normal tissues ( Bi and Wang, 2021 ). Moreover, the study identified correlations between LINC00472 low expressions and TNM stages, lymph node metastases and overall survival outcomes but not with gender and age ( Bi and Wang, 2021 ). A stable LINC00472 overexpressing PANC-1 cell line was established and subcutaneously inoculated into nude mice models to validate the in vivo effects of LINC00472.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations